The impact of Hashimoto’s thyroiditis on endoscopic thyroidectomy in patients with papillary thyroid carcinoma - Chen, Zhen-Xin; Chen, Jing-Bao; Pang, Feng-Shun; Lin, Zhan-Hong; Lin, Jian-Hong; Zheng, Wen-Wan; Liu, Qiu-Ping; Xu, Bo; Qin, You (Frontiers in Oncology, 2025)
BackgroundHashimoto’s thyroiditis (HT) is often associated with papillary thyroid carcinoma (PTC) and increases the difficulty of thyroidectomy. The clinical outcomes of applying the transoral approach and the transthoracic approach—the two most widely practiced endoscopic thyroid surgery techniques—in patients with PTC complicated by HT remain unclear.Materials and methodsThis study is a single-center retrospective design. Clinical data on 500 patients with PTC who underwent endoscopic thyroidectomy between January 2016 and December 2022 were collected. Patients voluntarily chose either the transoral endoscopic thyroidectomy via a vestibular approach (TOETVA) or endoscopic thyroidectomy via a chest-breast approach (ETCB), were grouped accordingly, and were further subdivided into HT and non-HT groups.ResultsOf 500 patients included, 140 had HT and 360 did not. The proportion of patients with stage T1 tumors was larger in the HT group than in the non-HT group. All endoscopic thyroidectomies (202 ETCBs and 298 TOETVAs) completed successfully without conversion to open surgery. The total number of retrieved lymph nodes was larger in the HT group than in the non-HT group, but the number of positive lymph nodes was smaller. Among patients treated by ETCB, the operative time was longer and the incidence of complications (transient hypoparathyroidism and transient recurrent laryngeal nerve injury) was greater in the HT group than in the non-HT group. For patients treated by TOETVA, the operative time and incidence of complications did not differ significantly between groups.ConclusionsHT appears to be associated with less aggressive tumor characteristics. TOETVA could represent a preferable option compared with ETCB for managing PTC with concomitant HT, although further prospective studies are warranted to confirm these findings.